2010
DOI: 10.1093/carcin/bgq131
|View full text |Cite
|
Sign up to set email alerts
|

Stearoyl-CoA desaturase-1: a novel key player in the mechanisms of cell proliferation, programmed cell death and transformation to cancer

Abstract: As part of a shift toward macromolecule production to support continuous cell proliferation, cancer cells coordinate the activation of lipid biosynthesis and the signaling networks that stimulate this process. A ubiquitous metabolic event in cancer is the constitutive activation of the fatty acid biosynthetic pathway, which produces saturated fatty acids (SFAs) and monounsaturated fatty acids (MUFAs) to sustain the increasing demand of new membrane phospholipids with appropriate acyl composition. In cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
254
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(278 citation statements)
references
References 84 publications
11
254
0
13
Order By: Relevance
“…Furthermore, we found that UPATmediated up-regulation of these genes is required for the survival of colon cancer cells. Consistent with our results, SCD1, the main enzyme involved in the synthesis of monounsaturated fatty acids, has been shown to be required for cancer cell proliferation, survival, transformation to cancer (32), and cancer spheroids propagation (33). The Sprouty family of proteins, key regulators of ERK signaling, has been shown to be able to function as negative or positive regulators of tumor development and/or progression in a cell type-dependent manner (34).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, we found that UPATmediated up-regulation of these genes is required for the survival of colon cancer cells. Consistent with our results, SCD1, the main enzyme involved in the synthesis of monounsaturated fatty acids, has been shown to be required for cancer cell proliferation, survival, transformation to cancer (32), and cancer spheroids propagation (33). The Sprouty family of proteins, key regulators of ERK signaling, has been shown to be able to function as negative or positive regulators of tumor development and/or progression in a cell type-dependent manner (34).…”
Section: Discussionsupporting
confidence: 88%
“…Thereby, has been proposed a relationship between SCD1 activity and tumor growth. In several types of cancers, elevated SCD1 expression and activity have been detected (34).…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of evidence has recently emerged implicating the expression and activity of SCD1 in the proliferation and survival of cancer cells (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). We sought to understand whether pharmacologic inhibition of SCD1 might have therapeutic benefit in human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of reports have implicated SCD1 expression and activity in the pathogenesis of cancer (for review see ref. 4). Human SCD1 mRNA was found to be overexpressed in a variety of human cancers, including colon, esophageal, and hepatocellular carcinomas relative to the corresponding normal tissues (5).…”
Section: Introductionmentioning
confidence: 99%